2019
DOI: 10.1002/ppul.24470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, sex, race/ethnicity, and allergy status in obesity‐related pediatric asthma

Abstract: Rationale Obesity in children increases the risk for new asthma. How age, sex, race/ethnicity, and allergy status affect the relationship between obesity and asthma is unclear. This study describes the relationship between high body mass index (BMI) and incident asthma. Methods We conducted a retrospective cohort study to compare asthma incidence among normal weight, overweight, and obese 2 to 6, 7 to 11, and 12 to 17 year olds to define the effects of sex, race/ethnicity, and allergy status. Weight status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Although childhood obesity is indeed considered a global epidemic, few studies have assessed adiposity measures thoroughly, showing inconsistent results. Furthermore, epidemiological studies in children demonstrated that the risk of newly diagnosed asthma is not constant across the pediatric populations [ 19 ]. Several common disease-modifying factors including age, sex, ethnicity, the development of atopic conditions, and metabolic alterations significantly affect the onset and phenotypic characteristics of asthma [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although childhood obesity is indeed considered a global epidemic, few studies have assessed adiposity measures thoroughly, showing inconsistent results. Furthermore, epidemiological studies in children demonstrated that the risk of newly diagnosed asthma is not constant across the pediatric populations [ 19 ]. Several common disease-modifying factors including age, sex, ethnicity, the development of atopic conditions, and metabolic alterations significantly affect the onset and phenotypic characteristics of asthma [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sex and age are important confounders both in FA 14,21 and asthma. 22,23 Nevertheless, to verify this possibility in our database several linear models were designed to examine the effect of our predictors on the dependent variables. Comparing the effect of all the predictors on the other predictors' linear regression coefficients confirmed that age and sex were the two confounding variables present in our database.…”
Section: Discussionmentioning
confidence: 99%
“…For this matter, we ensured that all residual distributions were normal and checked variance equality with the Levene test. The literature suggests that both FA 21 and asthma 22,23 have different traits in boys and girls when studied separately. Consequently, normalization for sex was obtained through stratification into boys and girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is an independent risk factor for asthma 2,3 . Obese children with asthma have a substantial clinical and economic healthcare burden.…”
Section: Introductionmentioning
confidence: 99%